Is There a Relationship between Low Health Literacy and Smoking? - Rahman Panahi (Health Education & Health Promotion, 2015)
Aim: Identification of contributory factors in smoking and gaining insight into the roles played by each of these factors including health literacy (HL) may account for quitting or decreasing the prevalence of smoking. The aim of the current study was to identify the effects caused by different HL levels on smoking.Methods: 347 students inhabiting the dormitories of Shahid Beheshti University of Medical Sciences were included in a cross-sectional correlational study. Random cluster sampling was used for the selection of participants. HELIA questionnaire (used for HL measurement in Iranian urban population between 18-65 years of age) and a researcher-made questionnaire (for determining the status of smoking in individuals) were used to collect information from the participants. All data were statistically analyzed by SPSS software.Findings: The mean and standard deviation of HL score was 70.52±14.12 out of 100. The results indicated that among the university students, 59.7% (201 people) were non-smokers, 23.1% (78 people) were smokers, and 17.2% (58 people) had experienced smoking. These findings reveal that HL is significantly correlated with smoking in university students. Also different levels (insufficient, relatively sufficient, and sufficient) of HL show its significant correlation with smoking, meaning that less HL levels are accompanied by a higher chance of smoking.Conclusion: The relatively high prevalence of smoking in university students and the impact of HL on smoking highlight the need to increase the level of HL in university students and develop an efficient tool for measuring smoking literacy in all age groups.